(untitled) (International Journal of Biology and Chemistry, 2020)
The application of comparator instrumental neutron activation analysis combined with the internal standard method and counting of the induced activity by a planar type HPGe detector was considered to determine 11 lanthanides by the long-lived radionuclides in the geological samples characterized by the enhanced thorium contents. These objects enabled to use thorium as the internal standard with its mass fraction of the samples found by the reliable method of instrumental gamma-spectrometry. Several certified reference materials of geological objects were used to verify the possibility of carrying out the corresponding routine analysis by the III category of precision according to the industrial standard OST 41-08-221-04. The method was demonstrated to analyze thorium-containing ore samples from Shock-Karagai rare earth deposit (North Kazakhstan) and some rare metal ore samples for lanthanide contents.